Efektivitas Penegakan Hukum Pasar Modal terhadap Pelaku Fraud Investasi - Rahmansyah Siregar; Zulfikri Toguan; Fadhlan Dwi Juliardi Albana (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study was prompted by the increase in investment activity in the Indonesian stock market, which has been accompanied by the emergence of various types of investment fraud, such as market manipulation, insider trading, the dissemination of false information, and online fraud. The objectives of this study are to assess the effectiveness of law enforcement against investment fraud in the Indonesian stock market, identify existing problems in its implementation, and formulate ways to strengthen legal protection for investors. The method used is normative legal research with an approach to applicable laws, concepts, and existing cases. Legal data is analyzed qualitatively using a descriptive-prescriptive method. The results of the study indicate that Indonesia already has a solid legal foundation through the Capital Market Law and the authority of the OJK, but its implementation is not yet fully effective. Key challenges include the weak deterrent effect of sanctions, the difficulty of proving violations in the stock market, an insufficient response to digital fraud, and the need for alignment between capital market laws and electronic transaction regulations. Strengthening supervision, digital evidence, and mechanisms to recover investors’ losses are crucial steps to enhance legal protection in the Indonesian stock market.